2014
DOI: 10.1603/ec13428
|View full text |Cite
|
Sign up to set email alerts
|

Within-Plant Distribution of <I>Aulacorthum solani</I> (Hemiptera: Aphididae), on Various Greenhouse Plants With Implications for Control

Abstract: Foxglove aphid, Aulacorthum solani (Kaltenbach) (Hemiptera: Aphididae), has recently undergone a status change from an occasional pest to a serious pest in greenhouses of North America and the United Kingdom. Little nonanecdotal information exists on the ecology of this insect in greenhouse crops. To help improve integrated pest management decisions for A. solani, the within-plant distribution of this pest was explored on a variety of common greenhouse plants in both the vegetative and flowering stage. This ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Only when aphids were allowed to naturally distribute on plants did species preferences emerge. M. persicae , which strongly colonized meristematic tissues, was preferred over A. solani , which generally prefers older leaves . Such prey–species interactions with colony density and location can have important implications for control outcomes.…”
Section: Morphology Distribution General Biology and Ecology Of A mentioning
confidence: 99%
“…Only when aphids were allowed to naturally distribute on plants did species preferences emerge. M. persicae , which strongly colonized meristematic tissues, was preferred over A. solani , which generally prefers older leaves . Such prey–species interactions with colony density and location can have important implications for control outcomes.…”
Section: Morphology Distribution General Biology and Ecology Of A mentioning
confidence: 99%
“…; Jandricic et al. ) and two species of natural enemies. The two species of natural enemies we evaluated were the parasitoid, Aphidius ervi Haliday (Hymenoptera: Braconidae), and the predatory brown lacewing, Micromus variegatus (Fabricius) (Neuroptera: Hemerobiidae).…”
Section: Introductionmentioning
confidence: 99%
“…In soybean aphid research, the number of aphids per plant has been used to index plant damage grade (Xiao et al 2013). However, for foxglove aphid, the number of foxglove aphids was not highly correlated with the total plant damage grade (Jandricic et al 2014). Thus, these two damage grades, TPD and PLD, were used for further analysis.…”
Section: Foxglove Aphid Resistance Evaluationmentioning
confidence: 93%
“…In spite of its economic importance, research about foxglove aphid has been very limited compared to soybean aphid in terms of biology, ecology, and effective control methods. Previous reports suggested that foxglove aphid prefers fresh tissues; however, recent research indicated that mature leaves are preferred over growing tips or young leaves (Jandricic et al 2014). Raso1, a foxglove aphid resistance QTL, was isolated from the cultivar 'Adams' (Weiss 1953) and mapped on chromosome 3 (Ohnishi et al 2012).…”
Section: Introductionmentioning
confidence: 99%